Exploring the Distribution of Direct Payments of the Common Agricultural Policy - Franz Sinabell; Erwin Schmid; Markus F. Hofreither (Austrian Institute of Economic Research (WIFO), 2008)
Direct payments are the most important expenditure of the Common Agricultural Policy. They are mostly in the form of decoupled direct payments which are intended to be allocatively neutral. Increasing volumes of such transfers imply that distributive aspects of CAP expenditures become more important. This paper looks at this issue by calculating various measures of concentration based on statistics on recipients of direct payments covering the period of 2000 to 2006. The findings are evaluated in the context of the objectives of the CAP and the review of the financial framework, due to be discussed in late 2008.
Keywords: 330; common agricultural policy; distribution of transfers; single farm payments; direct payments; EU-Agrarpolitik; Agrarsubvention; Verteilungswirkung; EU-Staaten